2007
DOI: 10.4102/curationis.v30i3.1102
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among nurses in a public hospital in Gauteng

Abstract: Introduction: The nursing profession in South Africa has lost skilled nurses due to intense international recruitment drives. The public hospital in this study has also failed to recruit and retain skilled nurses. The shortage of skilled nurses has led to deterioration in patient nursing care.
The aim of this study: The aim of this study was to describe the level of job satisfaction among nurses in a public hospital.
The methodology: A quantitative, descriptive survey was conducted. The data were…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
17
1
1
Order By: Relevance
“…It was observed that 60% of the respondents had average level of job satisfaction, while those with high levels of job satisfaction were 34.5% of the respondents; in addition 6 respondents had low level of job satisfaction which is equivalent to 5.5% of the respondents. This is in contrast to the level of job satisfaction that was discovered among nurses in South Africa [21] in which 42% of the South African nurses had low levels job satisfaction. Furthermore, different levels of job satisfaction have also been identified among other occupations.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…It was observed that 60% of the respondents had average level of job satisfaction, while those with high levels of job satisfaction were 34.5% of the respondents; in addition 6 respondents had low level of job satisfaction which is equivalent to 5.5% of the respondents. This is in contrast to the level of job satisfaction that was discovered among nurses in South Africa [21] in which 42% of the South African nurses had low levels job satisfaction. Furthermore, different levels of job satisfaction have also been identified among other occupations.…”
Section: Discussioncontrasting
confidence: 81%
“…Selebi and Minnaar describe levels of job satisfaction using the Minnesota Satisfaction questionnaire among nurses in Gauteng, South Africa, and reported that generally nurses experienced low satisfaction (42%) with the aspects of their job such as motivation, opportunity for creativity, innovation and responsibility. They also found very low levels of job satisfaction (22%) with aspects of their job such as supervision, working conditions, work policies, job security and salaries [21,30].…”
Section: Discussionmentioning
confidence: 99%
“…34 Extrinsic rewards and professional opportunities were the aspects of the job that were most commonly found to be dissatisfying by particpants in this study; other studies from Malawi and South Africa also found nurses to be dissatisfied with these particular subscales. [22][23][24] The findings in several of the previous studies reviewed 3,33,34,35 suggest moderate satisfaction among nurses, which is consistent with the findings of this study. These studies further suggest some satisfying and dissatisfying elements of the nursing profession across various cadres of nurses and cultures.…”
Section: Nurses' Job Satisfactionsupporting
confidence: 89%
“…8,20,21 Such behaviours are associated with job dissatisfaction among nurses. [22][23][24] Patient and public complaints about the quality of nursing care in Malawi may be related to negative attitudes among nurses who are dissatisfied with their jobs. This study was conducted to investigate the relationship between nurses' job satisfaction and attitudes towards nursing care at Mzuzu Central Hospital in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner, in South Africa, an investigation by Selebi revealed that nurses were experiencing low satisfaction with both the motivational (recognition, independence, and creativity) and the hygienic aspects (working conditions, job security and, remuneration) of their jobs [77]. In Malawi and Afghanistan, research by Fogarty et al on job satisfaction and health workers produced the same result [78]; their sample of nurses in Malawi showed that job satisfaction correlated positively with all four facets of work environment evaluation: recognition, training opportunities, being paid an appropriate salary, and safety in the workplace.…”
Section: Determinants Of Satisfactionmentioning
confidence: 99%